Overview Of Rules Governing Attribution Profits Generated From Permanent Establishment - Hamdan, Mohammad Abdul-Jalil (Advances in Social Sciences Research Journal, 2019)
In regard to the attribution of profits; this article concluded that there are still some uncertainties on the categorization on the taxation of the cross border businesses. Therefore, the OECD MTC has tried to harmonize the problem by employing some factual and functional evaluation of the challenges in the internal dealings. However, some countries mostly in the European Union had different methods that help in dealing with these problems. The paper on the other hand has tried to evaluate the solution in both treaty and non-treaty cases so as to achieve an amicable solution towards the same. In addition, the problem of double taxation still derives varied opinions by different commentaries by the United Nations and the OECD. The approach that has being proposed by the OECD MTC recently does not cover all the required areas of the problem. The hypothetical evaluation by the organization still faces some notable drawbacks in its implementation. The measures that have been employed so far do not uphold certainty to the individual taxpayers and businesses. Hence, the reliance of the authorities and business in these cases on documentation has been excessive. The paper establishes that the most ideal systems that would solve the current tax challenges are the one that would logically look at the inconsistencies observed in taxation. Therefore, the chapter proposes international discussions and agreements by use of a common and comparative law as the best way to achieve the desired taxation objectives. Thus, in order to protect the sovereignty of the countries and to ensure and confirm tax neutrality and fairness between source and residence countries, we are urgently in need to modify the current system of international taxation standards in accordance with new e-commercial environment. Furthermore, in pursuant to the basic principles of international tax law and to find better and essential solutions to the e-commerce issues relating to attribution of profits.